Multi-annual variations in the heat load of Poland - Okoniewska, Monika (Quaestiones Geographicae, 2024)
This study analyses multi-annual variations in biothermal conditions recorded at three weather stations in Kołobrzeg, Poznań and Kraków from 1951 to 2020 at 12:00 UTC based on the Universal Thermal Climate Index (UTCI). The analyses covered the median, lower and upper quartiles and average minimum and maximum UTCIs for respective months. In addition, the study determined the frequency of occurrence of various types of thermal stress in respective months. A significant rise in the annual and monthly trends was observed, while the highest increase was noted in winter and early spring (from January to May).